Commercial opportunities for gold catalysts - J. McPherson (The Southern African Institute of Mining and Metallurgy, 2009)
In order to add value to South Africa?s gold reserves AuTEK, a joint venture between Mintek and Anglogold-Ashanti, was started in 2000 with the aim of developing new industrial uses for gold. Accordingly gold catalysts are being made in kilogram quantities by Project AuTEK and sold toend users and other interested parties under the trade name AUROliteTM. Although these materials are optimized for use in CO oxidation applications, demonstration of appropriate activity, selectivity and durability in both liquid- and other gas-phase reactions has been shown1. The review below highlights the recent use of these materials, and other gold catalysts, in reactions of commercial interest.